An overview of water quality regulation or standards in swimming pools, drinking water, and hot springs in Germany, Canada, and Colombia - Sanchez Londoño, Yuly Andrea; Mehrvar, Mehrab; McCarthy, Lynda; Quiñones-Bolaños, Edgar; Rodriguez Cheu, Luis Eduardo; Reuss, Alexander; Romero Rojas, Jairo Alberto (Asociación Colombiana de Facultades de Ingeniería - ACOFI, 2022)
This article presents the regulations in the quality of water in swimming pools and drinking water in Germany, Canada, and Colombia, with a comparison to existing regulations and standards of quality of hot springs. Canada, Germany, and Colombia stipulate that drinking water must be free from unsafe levels of substances chemicals and pathogens, specifying guidelines for the microbiological and chemical parameters. However, in the case of hot springs Canada and Germany do not possess specific regulations or standards, but apply the same microbial and chemical requirements for swimming pools according to Public Swimming Pools Regulation of Canada and the standard DIN 19643 as well as the Infection Protection Act of Germany. Colombia does not have regulations or standards pertaining to the quality of hot springs, as established in article 6 of Decree 554 of 2015, and it does not apply the swimming pool regulations to hot springs.

Este artículo presenta las regulaciones en la calidad del agua en piscinas y agua potable en Alemania, Canadá y Colombia, mediante una comparación con la regulación existente y los estándares de calidad de las aguas termales. Canadá, Alemania y Colombia estipulan que el agua potable debe estar libre de niveles inseguros de sustancias químicas y patógenas, especificando guías para los parámetros microbiológicos y químicos. Sin embargo, en el caso de las aguas termales, Canadá y Alemania no poseen regulaciones o estándares específicos, pero aplican los mismos requisitos microbianos y químicos para piscinas, de acuerdo con el Reglamento de piscinas públicas de Canadá y la norma DIN 19643, tanto como la ley de protección contra infecciones de Alemania. Colombia no cuenta con reglamentos o normas sobre la calidad de las aguas termales, tal como lo establece el artículo 6 del Decreto 554 de 2015 y no aplica la regulación de piscinas a aguas termales.
Keywords: Drinking water; Hot springs; Regulations; Standards; Swimming pool; Agua potable; Termales; Reglamentos; Normas; Piscina